SISTEM JUAL BELI BAHAN BAKAR KENDARAAN PADA POM MINI DI PURWOKERTO UTARA - Dian Permana; Mukhlisin; Fetri Fatorina; Mukhtarzain, AA; Hidayat, Ariko (INUMIYA: Jurnal Ekonomi Pembangunan, 2025)
Guidelines for implementing buying and selling transactions refer to muamalah fiqh. Muamalah Fiqh has several principles or principles such as the principle of permissibility, the principle of mutual consent, the principle of justice, the principle of mutual benefit, the principle of mutual assistance, and the principle of writing. Apart from that, muamalah jurisprudence also prohibits tadlis, taghrir, najsy, ikhtikar, maysir, gharar and usury in every transaction. In reality, tadlis often occur and are practiced in people's lives. Based on this, it can be seen that there are two systems for selling fuel at mini stations, namely a permitted system and a system that is not permitted. The permitted buying and selling system is a sales system that uses a murabahah contract, the system obtains profits without elements of injustice between the parties in accordance with the rules and policies of the gas station. A fuel buying and selling system that is not permitted is a buying and selling system that takes as much profit as possible by reducing the dosage, thereby giving rise to an element of injustice towards one of the parties. In general, the practice of selling fuel at mini stations is prone to the practice of changing quantities or reducing quantities to make a profit.